Serum-stable RNA aptamers to urokinase-type plasminogen activator blocking receptor binding - Dupont, Daniel Miotto (Cold Spring Harbor Laboratory Press, 2010)
The serine proteinase urokinase-type plasminogen activator (uPA) is widely recognized as a potential target for anticancer therapy. Its association with cell surfaces through the uPA receptor (uPAR) is central to its function and plays an important role in cancer invasion and metastasis. In the current study, we used systematic evolution of ligands by exponential enrichment (SELEX) to select serum-stable 2′-fluoro-pyrimidine-modified RNA aptamers specifically targeting human uPA and blocking the interaction to its receptor at low nanomolar concentrations. In agreement with the inhibitory function of the aptamers, binding was found to be dependent on the presence of the growth factor domain of uPA, which mediates uPAR binding. One of the most potent uPA aptamers, upanap-12, was analyzed in more detail and could be reduced significantly in size without severe loss of its inhibitory activity. Finally, we show that the uPA-scavenging effect of the aptamers can reduce uPAR-dependent endocytosis of the uPA–PAI-1 complex and cell-surface associated plasminogen activation in cell culture experiments. uPA-scavenging 2′-fluoro-pyrimidine-modified RNA aptamers represent a novel promising principle for interfering with the pathological functions of the uPA system.